2020
DOI: 10.21203/rs.3.rs-31924/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for esophagojejunal anastomotic leakage in curative total gastrectomy combined with D2 lymph node dissection for gastric cancer: A retrospective cohort study

Abstract: Background: This study aimed to explore the risk factors associated with esophagojejunal anastomotic leakage (EJAL) in curative total gastrectomy combined with D2 lymph node dissection for gastric cancer.Methods: 390 consecutive patients receiving Roux-en-Y esophagojejunostomy reconstruction after surgery were reviewed. Multivariate analysis was performed using a logistic regression model to identify independent risk factors for EJAL.Results: Of the 390 patients enrolled in this study, EJAL occurred in 10 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Two studies reported that age is an independent risk factor of EJAL in multivariate analysis [ 12 , 13 ]. Xing et al [ 12 ] collected 390 patients and demonstrated that an age greater than 65 is closely related to the risk of developing anastomotic leakage (P: 0.043; OR: 3.882; 95% CI: 1.045–14.422).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that age is an independent risk factor of EJAL in multivariate analysis [ 12 , 13 ]. Xing et al [ 12 ] collected 390 patients and demonstrated that an age greater than 65 is closely related to the risk of developing anastomotic leakage (P: 0.043; OR: 3.882; 95% CI: 1.045–14.422).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that age is an independent risk factor of EJAL in multivariate analysis [ 12 , 13 ]. Xing et al [ 12 ] collected 390 patients and demonstrated that an age greater than 65 is closely related to the risk of developing anastomotic leakage (P: 0.043; OR: 3.882; 95% CI: 1.045–14.422). Kanaji et al [ 13 ], in their prospective study with 185 patients, set 75 years old as the threshold to make the variable significant on anastomosis leak risk (P: 0.0097; OR: 7349; 95% CI: 1.63–39.475).…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, there were constant discussions on theories for factors of postoperative AL. Some of the factors were accepted by most researchers, including malnutrition, hyper-tensility on the anastomotic stoma, lack of blood supply or local inflammation around anastomotic regions 8 , 11 , 23 . Other possible factors include advanced ages, high BMI, medical history of neoadjuvant chemotherapy, low hemoglobin 7 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative anastomotic leakage remains to be clinically concerning with an incidence of 2.1-14.6% and a mortality rate of up to 50% reportedly, which could cause prolonged hospital stay, increased overall cost, and even compromised long-term survival [4][5][6][7]. Present methods for detecting postoperative AL mostly depend on laboratory examination and radiological diagnosis [8] . However, in case of severe complications like AL, advanced medical treatment before clinically confirmed could seize the opportunity and greatly enhance curative effect [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical and experimental studies have been conducted to increase the safety of anastomoses and primary repaired injuries (gastric or duodenal perforation), thereby decreasing the incidence of these complications (5,6). Through several trials, a variety of materials have been evaluated to decrease the incidence of leakage and any related consequences (7)(8)(9).…”
mentioning
confidence: 99%